2023
DOI: 10.3390/biom13040591
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genome Analysis for Immune Cells Provides Clues for Stratification of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is caused by a combination of genetic and environmental factors. Recently, analysis of a functional genome database of genetic polymorphisms and transcriptomic data from various immune cell subsets revealed the importance of the oxidative phosphorylation (OXPHOS) pathway in the pathogenesis of SLE. In particular, activation of the OXPHOS pathway is persistent in inactive SLE, and this activation is associated with organ damage. The finding that hydroxychloroquine (HCQ), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(59 reference statements)
2
2
0
Order By: Relevance
“…Despite its reliance on a limited sample size, the study reports significantly elevated SLC15A4 mRNA in PBMCs from SLE patients compared to healthy controls. This observation bolsters the association between SLC15A4 expression and autoimmune diseases such as SLE (50).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Despite its reliance on a limited sample size, the study reports significantly elevated SLC15A4 mRNA in PBMCs from SLE patients compared to healthy controls. This observation bolsters the association between SLC15A4 expression and autoimmune diseases such as SLE (50).…”
Section: Discussionsupporting
confidence: 58%
“…Immune dysregulation, wherein an overactive immune system generates autoantibodies against the body's cells and tissues, is a hallmark of SLE. Furthermore, the fact that SLE is characterized by heightened levels of type I interferons (IFN-I) makes the association between SLC15A4 and IFN-I production especially noteworthy (17,50,52). Excessive IFN-I production is a significant contributor to SLE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its reliance on a limited sample size, the study reports significantly elevated SLC15A4 mRNA in PBMCs from SLE patients compared to healthy controls. This observation bolsters the association between SLC15A4 expression and autoimmune diseases such as SLE [49].…”
Section: Discussionsupporting
confidence: 58%
“…unpublished data). Actually, the analysis using the expression quantitative trait loci (eQTL) database, ImmuNexUT, has shown that the expression of SLC15A4 is increased in individuals with SLE-risk genotypes ( 45 ). A further analysis of the functional significance of SNPs in pathogenesis is needed, as with other disease-related SNPs; however, the above observation obtained by an eQTL analysis is consistent with the results of animal model experiments, indicating that SLC15A4 plays a role in lupus pathogenesis.…”
Section: Control Of Mtorc1 By Slc15a4mentioning
confidence: 99%